PERTUMBUHAN DAN HASIL BEBERAPA VARIETAS CABAI MERAH PADA MEDIA TUMBUH YANG BERBEDA - Ainun Marliah; Mariani Nasution; Armi Armi (Jurnal Floratek, 2011)
The study was aimed at determining appropriate varieties and growing media on growth and yield of red peppers as well as interactions between the two factors mentioned. The experimental design used was a completely randomized design (CRD) 3 x 3 with three replications. Factors studied were red pepper varieties (TM 999, ST 168 and local), and growing media (soil + sand, soil + manure, and soil + husk) with a ratio of 2:1. The results showed that varieties exerted highly significant effects on plant height at 15 days after transplanting (DAT) and fruit weight per plant at first harvest 90 DAT and a significant effect on number of fruits per plant at first harvest 90 DAT. Varieties of TM 999 and ST 168 were better than that of local. Growing media also exerted highly significant effects on plant height at 45 DAT, number of productive branches, number of fruits per plant at first harvest (90 DAT) and fruit weight per plant at first harvest (90 DAT), and significant effects on plant height at 15 and 30 DAT, number of fruits per plant at second harvest (93 DAT), and weight of fruit per plant at third harvest (96 DAT). The best growing medium was soil + sand. There was no significant interaction between varieties and growing media on growth and yield of red chili.